The effect of unconventional monetary policy on inflation expectations: Evidence from firms in the United Kingdom - Lena Boneva; James Cloyne; Martin Weale; Tomasz Wieladek (Bank of England, External Monetary Policy Committee Unit, 2016)
This paper investigates the effect of quantitative easing (QE) and other unconventional monetary policies on inflation and wage expectations of UK manufacturing firms. To identify the effect of QE on firms' expectations, we use a novel approach of combining microeconometric data with macroeconomic shocks: QE is exogenous to inflation expectations of individual firms, and so are other macroeconomic developments like aggregate inflation or GDP growth. We find that firms' inflation expectations increase by 0.22 percentage points in response to 50 billion of QE, implying that inflation expectations are part of the transmission mechanism of QE. In contrast, we find a positive but small and insignificant effect of forward guidance on inflation and wage expectations.
Keywords: D22; E52; E31; 330; Inflation expectations; firm survey data; unconventional monetary policy; quantitative easing